Association between social participation patterns and social adaptation among retired Tibetan immigrants: the mediating effect of institutional capital - Zhou, Yue; Ma, Menghe; Sun, Sheng (Frontiers in Public Health, 2024)
IntroductionThis study aims to examine the impact of various patterns of social participation on social adaptation among retired Tibetan immigrant older adults, as well as the mediating role of institutional capital in this relationship.MethodsA cross-sectional survey was conducted in Sichuan Province, China, involving 700 older adults who immigrated to Sichuan after retiring from Tibet. After excluding invalid samples, 501 were retained for the final analysis. Distinct patterns of social participation were identified using latent class analysis (LCA), and multiple regression models were employed to analyze the mediating role of institutional capital in the relationship between social participation patterns and social adaptation.ResultsThe study revealed four distinct patterns of social participation among the participants: full low-level participation, personal relationship-centric participation, social relevance-oriented participation, and balanced active participation. Institutional capital was found to play both a partial and a full mediating role in the relationship between social participation patterns and social adaptation.DiscussionThese findings suggest that the social participation of retired immigrant seniors is influenced by the combined effects of role change, spatial transition, and aging, highlighting the urgent need to identify alternatives prior to integration into the local community to facilitate a smoother adaptation to life in their new environment.